ATG14L and ZBTB16: Critical Roles in Aggrephagy in STHdhQ7/Q7 Striatal Neurons - Kissner, Vanessa (Université d'Ottawa / University of Ottawa, 2020)
Huntington’s disease (HD) is a devastating neurodegenerative disease caused by a polyglutamine expansion repeat in exon one of the gene encoding the huntingtin protein. A hallmark of HD pathology is the accumulation of aggregates of the mutant huntingtin protein (mHtt). Macroautophagy (MA) is an intracellular catabolic process responsible for the degradation of cytoplasmic constituents, including misfolded protein aggregates, as are found in HD. Selective MA which degrades protein aggregates is known as aggrephagy. Recently, chronic blockade of the metabotropic glutamate receptor subtype 5 (mGluR5) in the zQ175 HD mouse model has been shown to cause an improvement in disease progression, which correlated with an activation of the GSK3-mediated pathway of MA. A reduction in ZBTB16, a core component of the ZBTB16-Cullin3-Roc1 E3 ubiquitin ligase complex, and an increase in ATG14L, a key component of the vps34 complex responsible for autophagosome biogenesis, were evident following mGluR5 inhibition in zQ175 HD mice. In the present study, we have found that silencing of ATG14L using CRISPR Cas9 in STHdhQ7/Q7 striatal neurons causes an inhibition of MA, a unique post-translational modification on beclin-1, decreased mGluR5 expression, and the accumulation of Q138 (mHtt). We find that CRISPR-Cas9-induced silencing of ZBTB16 in STHdhQ7/Q7 striatal neurons causes an induction of MA, decreased mGluR5 expression, and the clearance of Q138 (mHtt). ZBTB16 likely exerts its effects on MA via regulation of ATG14L. These findings elucidate the important role of ATG14L and ZBTB16 in aggrephagy in STHdhQ7/Q7 striatal neurons, and suggest that the modulation of ATG14L and ZBTB16 may represent novel therapeutic approaches in the treatment of HD.
Keywords: Autophagy; Aggrephagy; mGluR5; Huntington's Disease; ATG14L; ZBTB16